EVALUASI KESESUAIAN LAHAN SAWAH PASCA BANJIR BANDANG PADA TANAMAN PADI DI KABUPATEN ACEH TENGGARA - Nani Kitti Sihaloho; Desi Sri Pasca Sari Sembiring (JURNAL AGROTEKNOSAINS, 2019)
The aim of the study was to determine the level of suitability of wetland rice fields in the area before flash floods and post flash floods Lawe Tua Makmur Village, Lawe Alas Subdistrict, Southeast Aceh Regency and soil analysis at the Research and Development Laboratory of PT. Nusa Pusaka Kencana Analytical & Qc. Laboratory Bahilang Tebing Tinggi Medan in April 2016 and December 2017. It is carried out by a survey method that refers to the extent of the limiting factor of land characteristics. Data from observations in the field and data from laboratory analysis were matched to the criteria for the suitability of wetland rice classes. The results showed that the actual land suitability class for paddy rice in the area prior to banjir bandang was according to marginal / S3 (r, f) and the potential land suitability class was marginal / S3 (r). Actual land suitability class for wetland crops in the post-banjir bandang area according to marginal / S3 (r, f, n) and potential land suitability classes according to marginal / S3 (r). The limiting factor is the permanent texture of the soil so that it cannot be repaired and the limiting factors of CEC, organic C and N-total can still be improved by adding organic matter and fertilizing with nitrogen.